Gender and violence in historical and contemporary perspectives: situating India - Atwal, Jyoti; Fleßenkämper, Iris (Taylor & Francis Group, 2019)
Cover -- Half Title -- Title -- Copyright -- CONTENTS -- List of contributors -- Preface -- PART I Introduction -- Situating India: challenges and propositions -- Researching gender-based violence in India: issues, concepts, approaches -- PART II Historical encounters and cultures of violence -- 1 Of devotional zeal and patriarchal norms: gender and violence in the Periya Purāṇam -- 2 Silenced women, speaking men: locating gendered epistemic violence in nineteenth century German representations of India -- 3 Gendered behaviour: religious norms and sexual deviance in the Basel India Mission in the first half of the nineteenth century -- 4 Bodies in pain: violence and sexually 'deviant' male and transgender bodies in colonial India, 1862-1922 -- 5 Sati, childwives, and prostitutes: constituting violence and criminality in colonial India -- PART III Minorities and marginalised women: sexuality and violence -- 6 Unregistered concerns: violence against women with disabilities in India -- 7 Nature of violence against Dalit women -- 8 A genealogy of Muslim feminism in Maharashtra: systems and violence -- 9 Hijras: India's third gender between discrimination and recognition -- PART IV Economies of violence and cultural representations -- 10 The Nirbhaya murder case: women as the oddity in public transport -- 11 Gender-based violence of economic globalisation in contemporary India: an intersectional approach to gender and violence -- 12 Fifty Shades of Grey: a romance that we cannot resist? -- 13 Gender, violence, and resistance in Partition narratives -- 14 On behalf of us all? Violence against women as a subject of Indian film studies -- Index.